Ethanolic Extract of Mangosteen (Garcinia mangostana) Peel Inhibits T47D and Hela Cells Line Proliferation Via Nf-kB Pathway Inhibition - Rivanti, Erlina; Rohmah, Annishfia Lailatur; Putri, Herwandhani; Tirtanirmala, Prisnu; Pamungkas, Dyaningtyas Dewi Putri (Indonesian Journal of Cancer Chemoprevention, 2012)
Effective and selective chemoterapeutic and chemopreventive agent is needed to cure breast and cervical cancers. One of the potential natural material is mangosteen peel (Garcinia mangostana). In this study, we observed cytotoxic effect of ethanolic extract of mangosteen peel (EMP) on HeLa cells line and T47D cells line. The cytotoxic effect was determined using MTT assay. EMP showed cytotoxic effect on T47D cells and HeLa cells with IC50 values of 2.07 μg/ml and 10.58 μg/ml respectively. Molecular docking simulation was done to predict the molecular mechanism of active compund in mangosteen peel extract, α-mangostin, in NFκB pathway which is one of the potential pathway to induce cytotoxicity on T47D and HeLa cells. Docking was done using PLANTS software and the binding score between α-mangostin and proteasom is -78,12, whereas the binding score between α-mangostin and IKK is -86.84. These results showed the possiblity mechanism of mangostin peel extract containing α-mangostin inhibits IKK activation in NFκB pathway. Based on this study, we conclude that mangosteen peel extract is potential to be developed as chemopreventive agent toward cervical and breast cancers.Keywords : Mangosteen peel (Garcinia mangostana), cytotoxic, T47D cells, HeLa cells, NFκB